2021
DOI: 10.1186/s13018-021-02253-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for femoral fracture in lateral decubitus direct anterior approach total hip arthroplasty using conventional stems: a retrospective analysis

Abstract: Objective To provide guidelines for surgery and reduce the incidence of fracture, this study analyzed the relationship between femoral fracture and related factors in direct anterior approach (DAA) total hip arthroplasty (THA) in the lateral decubitus position. Method A retrospective series of 273 consecutive patients who underwent THA with the DAA in the lateral decubitus position was analyzed. Each surgery was performed by the same surgeon with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In spite of the above mentioned advantages, the DAA is not the panacea of surgical approaches to the hip, as it has been associated with a significant learning curve (23)(24)(25)(26) an increased risk of lateral femoral cutaneous nerve neuropraxias (15,27), higher rates of intra-operative femoral fractures (15,28), greater rates of early femoral revision (29,30) (LFCN and an increased risk of wound complications (31,32).…”
Section: Current Perspectives Of South African Orthopaedic Surgeons T...mentioning
confidence: 99%
“…In spite of the above mentioned advantages, the DAA is not the panacea of surgical approaches to the hip, as it has been associated with a significant learning curve (23)(24)(25)(26) an increased risk of lateral femoral cutaneous nerve neuropraxias (15,27), higher rates of intra-operative femoral fractures (15,28), greater rates of early femoral revision (29,30) (LFCN and an increased risk of wound complications (31,32).…”
Section: Current Perspectives Of South African Orthopaedic Surgeons T...mentioning
confidence: 99%
“…Currently, it is recognized that the main reasons for fracture are the improper practice and the difference in stiffness between the bone and implant 12 . OP is also a predisposing factor for the intraoperative fracture in the femoral isthmus because of the reduction in bone density and deterioration of bone microarchitecture 13–15 . OP has been reported as the major cause of an estimated nine million osteoporotic fractures 16 .…”
Section: Introductionmentioning
confidence: 99%
“… 12 OP is also a predisposing factor for the intraoperative fracture in the femoral isthmus because of the reduction in bone density and deterioration of bone microarchitecture. 13 , 14 , 15 OP has been reported as the major cause of an estimated nine million osteoporotic fractures. 16 Previous studies showed that the rate of subsequent fracture decreased by 50% in patients who received osteoporosis treatment.…”
Section: Introductionmentioning
confidence: 99%